SISTEM INFORMASI PERSEDIAAN BARANG SEDERHANA PT. WISEMAN MULIA SEJAHTERA DENGAN APLIKASI BARANG DAN PERSEDIAAN BERBASIS ANDROID - Ade Alhadi; Desmy Riani; Yuggo Afrianto (JPMUJ, 2023)
PT. Wiseman Mulia Sejahtera previously used the manual method by collecting all data in and out of goods by recording them in the WhatsApp group "Exit and Exit Goods". This makes admins, supervisors, and directors of PT. Wiseman Mulia Sejahtera could not find relevant inventory information. The expected result of this research is that warehouse operations are computerized. The flow in completing this research system consists of needs analysis, development, implementation, and application testing. In this development using the Samsung Galaxy A51 Android Smartphone Android 12 One UI 4.1 version and Goods and Inventory Software from Chester SW Def. The result of this system is that admins, supervisors and directors can manage the availability of goods easily, carry out complete and computerized transactions. Based on the assessment interviews, the respondents who had been asked to informants stated that the results were very good with the Goods and Inventory application because it made PT.'s warehouse operations easier. Wiseman Mulia Sejahtera.